Implementasi Pembelajaran Core Ditinjau dari Kemampuan Memecahkan Masalah Matematika - Nasrulloh, Muhammad Farid; Faidah, Risky Solikah Nur; Umardiyah, Fitri; Zuhriawan, Muhammad Qoyum (EDUSCOPE: Jurnal Pendidikan, Pembelajaran, dan Teknologi, 2023)
ABSTRACT This study aims to determine whether there is an increase in students' problem-solving abilities after applying CORE (connecting, organizing, reflecting, extending) learning in mathematics learning and also whether the CORE model learning (connecting, organizing, reflecting, extending) is effective in terms of solving abilities. problems after the implementation of the CORE learning model. This research was conducted by the author on May 31, 2022 and June 8, 2022 at MTs bahrul 'UlumTambakberas Jombang. The research subjects were 25 students of class VII C on Statistics (Data Presentation). With the number of students 25 students. This research method uses a scoring system after the pretest and posttest. For data analysis, the author requires several stages of testing, namely validity test, reliability test, normality test, homogeneity test, and Paired Sample t Test. This study uses learning tools including Learning Implementation Plans (RPP) with the CORE learning model, Student Worksheets (LKPD), and Learning Outcomes Tests according to Students' Problem-Solving Ability which have been validated by two validators. The total average score of the two validators is 3.21 with a match percentage of 80.21%. This means that the test of learning outcomes according to students' ability to solve problems is very valid and feasible to use. KEYWORDS:CORE, Mathematics, problem_solving.   ABSTRAK Penelitian ini bertujuan untuk mengetahui apakah adanya peningkatan kemampuan pemecahan masalah bagi siswa setelah diterapkan pembelajaran CORE (connecting, organizing, reflecting, extending) di dalam pembelajaran matematika dan juga apakah pembelajaran model CORE (connecting, organizing, reflecting, extending) efektif ditinjau dari kemampuan pemecahan masalah setelah diterapkannya model pembelajaran CORE tersebut. Subjek penelitian sebanyak 25 orang siswa kelas VII C pada materi Statistika (Penyajian Data). Dengan jumlah siswa 25 Siswa. Metode penelitian ini menggunakan system hasil penilaian setelah dilakukannya pretest dan posttest. Analisis data penulis memerlukan beberapa tahapan uji yaitu uji kevalidan, uji reliabilitas, uji normalitas, uji homogenitas, serta Uji t Dua Sampel Berpasangan (Paired Sample t Test). Penelitian ini menggunakan perangkat pembelajaran meliputi Rencana Pelaksanaan Pembelajaran (RPP) dengan model pembelajaran CORE, Lembar Kerja Peserta Didik (LKPD), serta Tes Hasil Belajar menurut Kemampuan Siswa Memecahkan Masalah yang telah divalidasi oleh dua validator. Skor rata-rata total dari dua validator ialah 3,21 dengan presentase kecocokan 80,21%. Artinya tes hasil belajar menurut kemampuan siswa memecahkan masalah sangat valid dan layak untuk dipergunakan. KATA KUNCI: CORE, Matematika, Pemecahan_Masalah.